The impact of ownership on media content : An exploratory case study of Nation Media Group and Standard Newspaper Group; Kenya - Okech, Agutu Keven Steve (My University, 2008)
Media ownership has remained an intriguing factor in understanding the news production process. Various studies have proven that ownership influence do affect how journalists cover stories. The said influence takes various forms including direct censorship and coercion of editorial staff. This study critically examines how media ownership patterns, shape content in the Kenyan media. The researcher employs the use of thematic content analysis and coding of raw data retrieved from the internet sites of two leading Kenyan newspapers as outlined in the research methodology and findings chapters. The data retrieved from the internet sites of the two newspapers is then analysed to prove how ownership patterns influence daily news coverage. Of note is also the use of two case studies – The Nation and The Standard newspapers to analyse 905 articles written during the 2002 multiparty Kenyan elections. It emerges that ownership indeed influenced news coverage in the 2002 Kenyan elections. The emerging winner in the elections was also the candidate with the most coverage in the two newspapers. Also emergent is the factor that the election was widely personality driven. The implications of the research findings is that objectivity though practiced in some instances, was widely affected by the editorial line of the said newspapers. The editorial line was largely pegged to ownership influences in most cases.
Keywords: NO KEYWORDS